2014
DOI: 10.1111/nph.12729
|View full text |Cite
|
Sign up to set email alerts
|

Crown depth as a result of evolutionary games: decreasing solar angle should lead to shallower, not deeper crowns

Abstract: SummaryThere is a general notion in the literature that, with increasing latitude, trees have deeper crowns as a result of a lower solar elevation angle. However, these predictions are based on models that did not include the effects of competition for light between individuals. Here, I argue that there should be selection for trees to increase the height of the crown base, as this decreases shading by neighbouring trees, leading to an evolutionarily stable strategy (ESS). Because the level of between-tree sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Growth impairment was strongest for barnyard grass, where plant height, a major determinant of a plant’s ability to compete for light, as well as tiller number were also strongly negatively affected. Because plant height and traits such as leaf mass fraction, leaf area ratio, leaf mass per area and canopy area are correlated ( Falster and Westoby, 2003 ; Moles et al, 2009 ) and because plant height influences seed mass, time to reproduction and the number of seeds ( Moles and Leishman, 2008 ; Moles et al, 2009 ), we assume that the presence of buckwheat might affect the successful propagation of barnyard grass to a larger extent.…”
Section: Discussionmentioning
confidence: 99%
“…Growth impairment was strongest for barnyard grass, where plant height, a major determinant of a plant’s ability to compete for light, as well as tiller number were also strongly negatively affected. Because plant height and traits such as leaf mass fraction, leaf area ratio, leaf mass per area and canopy area are correlated ( Falster and Westoby, 2003 ; Moles et al, 2009 ) and because plant height influences seed mass, time to reproduction and the number of seeds ( Moles and Leishman, 2008 ; Moles et al, 2009 ), we assume that the presence of buckwheat might affect the successful propagation of barnyard grass to a larger extent.…”
Section: Discussionmentioning
confidence: 99%
“…The simulation results and behavior of individual‐based models can be explained by game theoretic analyses (Maynard Smith, ). Game theoretic approaches have been employed to solve mathematically for the most competitive trait combination(s) in a continuous multivariate trait distribution, such as the competitively optimal biomass allocation among leaves, stems, and fine roots (Dybzinski et al ., , , ; Farrior et al ., ,b), crown depth (Vermeulen, ), tree height (King, ; Falster & Westoby, ), leaf angles (Hikosaka & Hirose, ), and leaf area index (LAI; Anten, ). Although game theoretic mathematical analyses have been useful in explaining field observations and experimental results (e.g., Dybzinski et al ., ; Farrior et al ., ) and improving our understanding of simulation results from complex models (e.g., Weng et al ., ), their obvious disadvantage is the model simplicity they require.…”
Section: Introductionmentioning
confidence: 99%
“…In real forests, stands are not usually uniform and static, but Kuuluvainen's results are still interesting and relevant. Recently, Vermeulen () investigated an evolutionary model of nongrowing trees competing for light and found, in contrast to Kuuluvainen, that low sun angles resulted in the evolution of shallow crowns (i.e., top‐heavy crowns) and vice versa. Our model does not support the results by Vermeulen, as decreasing the sun angle always gives narrower, less top‐heavy trees.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Yokozawa, Kubota, and Hara () studied crown shape coexistence in an ecological time scale in a size‐structured model and found coexistence in some cases. A more recent example is Vermeulen (), who investigated the influence on light direction on the evolution of crown shapes, albeit in a forest without size structure. He showed that crown top‐heaviness (more precisely the crown ratio) was increasing, as the incident sun angle was decreasing.…”
Section: Introductionmentioning
confidence: 99%